IN-SILICO SCREENING OF PLANT-DERIVED NATURAL COMPOUNDS FOR THEIR ANTI- COVID-19 POTENTIAL - Anand, Vandita; Srivastava, Saumya; Pandey, Anjana (Journal of the Chilean Chemical Society, 2022)
The novel coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) began in Wuhan, China, in December 2019 and quickly spread across the worldwide. It becomes a global pandemic and risk to the healthcare system of almost every nation around the world. In this study thirty natural compounds of 19 Indian herbal plants were used to analyze their binding with eight proteins associated with COVID -19. Based on the molecular docking as well as ADMET analysis, isovitexin, glycyrrhizin, sitosterol, and piperine were identified as potential herbal medicine candidates. On comparing the binding affinity with Ivermectin, we have found that the inhibition potentials of the Trigonella foenum-graecum (fenugreek), Glycyrrhiza glabra (licorice), Tinospora cordifolia (giloy) and Piper nigrum (black pepper) are very promising with no side-effects.